2009
DOI: 10.1590/s0100-29452009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Preferential reproduction mode of hermaphrodite papaya plant (Carica papaya L; Caricaceae)

Abstract: -This research was done to study the reproductive system of papaya hermaphrodite plant based on the histochemical nature of pollen grain, stigma receptivity, in vivo pollen grain germination and pollen:ovule ratio. In the histochemical analysis, pollen grains were stained by using Sudan IV and I 2 KI solution; the stigma receptivity was assessed by alpha-naphthtyl acetate solution in closed and opened flowers. Pollen germination and pollen tube growing were examined in flower buds near anthesis with 0.1% anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Parés et al (2002) reported that in papaya plants, the stigmas can remain receptive for up to three days after anthesis, and the efficiency of artificial pollination was better in the first 48 hours after floral opening. Similar results were observed by Damasceno Júnior et al (2009), who reported greater stigma receptivity of papaya soon after anthesis, with receptivity continuing for up to 48 hours after floral opening.…”
Section: Stigma Receptivitysupporting
confidence: 88%
“…Parés et al (2002) reported that in papaya plants, the stigmas can remain receptive for up to three days after anthesis, and the efficiency of artificial pollination was better in the first 48 hours after floral opening. Similar results were observed by Damasceno Júnior et al (2009), who reported greater stigma receptivity of papaya soon after anthesis, with receptivity continuing for up to 48 hours after floral opening.…”
Section: Stigma Receptivitysupporting
confidence: 88%
“…Some crops have multiple mating systems, such as domesticated ‘Maradol’ ( Carica papaya ), which is hermaphroditic, while native varieties and wild papayas are dioecious ( Carvalho and Renner, 2012 ). Importantly, the characterization of the mating system of many plant species has been biased toward the domesticated counterparts, because only a sub-sample of the wild-to-domesticated complex was used (e.g., Carica papaya ( Damasceno et al, 2009 ), Persea americana ( Ish-Am et al, 1999 ), Piper nigrum ( Thangaselvabal et al, 2008 ). This bias may have profound consequences for the conservation of conspecific wild relatives, especially because conclusions drawn from studies with domesticated varieties are extrapolated to the whole species, failing to consider the genotypic and phenotypic diversity that wild relatives possess.…”
Section: Introductionmentioning
confidence: 99%
“…Hermaphrodite plants are typically used for commercial cultivation, which makes it important to understand their means of reproduction. The results indicated that the preferential means of reproduction of hermaphrodite papaya is facultative autogamous with cleistogamy (Damasceno Junior et al, 2009b).…”
Section: At Reproductive and Cytological Levelmentioning
confidence: 93%